Secondary battery and use thereof
Patent Information
- Application Number
- CN202610805636.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-06-05
AI Technical Summary
上述问题导致锂离子二次电池在低温环境下既无法满足高效快充的使用需求,其安全可靠性也难以得到有效保障
[0013]本申请实施例提供二次电池,通过正负极材料与正负极片的物理化学参数间的系统匹配,建立正极片平均直流内阻与二次电池平均直流内阻的比值a、与正负极Dv50粒径的比值b的关系式n=a×b,同时n满足0.009≤n≤0.252,实现正负极动力学的动态平衡,实现在低温环境下抑制析锂,并显著提升二次电池的低温快充性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and in particular to a secondary battery and its application. Background Technology
[0002] With its core advantages such as high energy density, long cycle life, and low self-discharge rate, lithium-ion batteries have become the core energy storage device in fields such as new energy vehicles, electrochemical energy storage systems, and portable electronic devices. As application scenarios continue to expand, the demand for their application in low-temperature conditions such as transportation in high-altitude and cold regions, outdoor cryogenic energy storage, and polar exploration equipment is becoming increasingly urgent.
[0003] However, low-temperature operating conditions have multiple significant negative impacts on the electrochemical performance and safety stability of lithium-ion batteries. On the one hand, the viscosity of the electrolyte increases dramatically at low temperatures, and the thickness of the lithium-ion solvation sheath layer increases significantly, causing an exponential decrease in the lithium-ion transport rate. This also increases the charge transfer resistance at the electrode-electrolyte interface, triggering polarization and causing a sharp decline in battery rate performance, making efficient fast charging impossible. On the other hand, at low temperatures, a large number of lithium ions cannot be embedded into the negative electrode lattice in time, and are reduced on the negative electrode surface, precipitating metallic lithium and forming lithium dendrites. These lithium dendrites continue to grow and extend with increasing cycle count, easily piercing the separator and causing internal short circuits. These problems mean that lithium-ion rechargeable batteries cannot meet the requirements for efficient fast charging at low temperatures, and their safety and reliability are also difficult to guarantee effectively.
[0004] Therefore, developing a lithium-ion rechargeable battery that combines excellent fast-charging performance with high safety and reliability under low-temperature conditions is of great significance for breaking through the bottleneck of low-temperature application of lithium-ion batteries and expanding their application boundaries. Summary of the Invention
[0005] This application provides a secondary battery that achieves a dynamic balance between the positive and negative electrode dynamics, suppresses the deposition of metallic lithium on the negative electrode surface, and simultaneously improves its fast charging performance.
[0006] This application also provides an electrical device including the aforementioned secondary battery, which can realize diverse application scenarios.
[0007] In a first aspect, embodiments of this application provide a secondary battery, the secondary battery comprising a positive electrode and a negative electrode, the positive electrode comprising a positive electrode material and the negative electrode comprising a negative electrode material;
[0008] The positive electrode material includes lithium iron phosphate, and the negative electrode material includes graphite-based materials;
[0009] The ratio of the average DC internal resistance of the positive electrode to the average DC internal resistance of the secondary battery is a.
[0010] The ratio of the Dv50 particle size of the positive electrode material to the Dv50 particle size of the negative electrode material is b;
[0011] n = a × b, where 0.009 ≤ n ≤ 0.252.
[0012] Secondly, embodiments of this application provide an electrical device including the aforementioned secondary battery.
[0013] This application provides a secondary battery. By systematically matching the physicochemical parameters of the positive and negative electrode materials and the positive and negative electrode sheets, a relationship is established between the ratio of the average DC internal resistance of the positive electrode sheet to the average DC internal resistance of the secondary battery (a) and the ratio of the Dv50 particle size of the positive and negative electrodes (b), with n=a×b. At the same time, n satisfies 0.009≤n≤0.252, thereby achieving a dynamic balance of positive and negative electrode dynamics, suppressing lithium plating in low-temperature environments, and significantly improving the low-temperature fast charging performance of the secondary battery. Detailed Implementation
[0014] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0015] As mentioned earlier, low-temperature environments significantly hinder the physicochemical processes within lithium-ion batteries (such as lithium-ion insertion / extraction, electrolyte ion conduction, and electrode interface charge transfer), leading to the deposition of metallic lithium on the negative electrode surface and compromising the safety performance of the rechargeable battery. The inventors discovered that the core cause of this low-temperature lithium deposition problem is the imbalance between the lithium-ion extraction and insertion rates within the battery. Therefore, this invention establishes a quantitative correlation between key parameters to precisely control the matching rate of lithium-ion extraction from the positive electrode and lithium-ion insertion from the negative electrode within the rechargeable battery. This effectively suppresses the deposition of metallic lithium on the negative electrode surface, simultaneously improving both low-temperature fast-charging performance and safety.
[0016] Based on this, the present invention proposes a secondary battery, which includes a positive electrode and a negative electrode. The positive electrode includes a positive electrode material, and the negative electrode includes a negative electrode material.
[0017] Positive electrode materials include lithium iron phosphate, and negative electrode materials include graphite-based materials;
[0018] The ratio of the average DC internal resistance of the positive electrode to the average DC internal resistance of the secondary battery is a.
[0019] The ratio of the Dv50 particle size of the positive electrode material to the Dv50 particle size of the negative electrode material is b;
[0020] n = a × b, where 0.009 ≤ n ≤ 0.252.
[0021] The secondary battery of the present invention achieves dynamic balance of positive and negative electrode dynamics through systematic matching between the physicochemical parameters of the positive and negative electrode materials and the positive and negative electrode sheets. Combined with the dynamic adjustment of parameters, it achieves a significant improvement in the low-temperature fast charging performance of the secondary battery while effectively suppressing the precipitation of metallic lithium.
[0022] It should be noted that the average DC internal resistance (average DCR) refers to the average value of the DCR at three temperatures: -10°C, 0°C, and 25°C. By adjusting the ratio 'a' of the average DCR of the cathode and the average DCR of the secondary battery, the rate at which lithium ions are extracted from the cathode active material lattice across the entire temperature range can be precisely controlled. Specifically, the average DCR of the cathode consists of three parts: average ohmic impedance, average charge transfer impedance, and average concentration polarization impedance. Adjusting 'a' essentially involves synergistically regulating the electron conduction efficiency in the cathode and the transport rate of lithium ions across the cathode / electrolyte interface, thereby achieving precise control over the rate at which lithium ions are extracted from the cathode lattice. This not only helps optimize the total amount of reversible lithium ion release during cycling, but also plays a key role in suppressing low-temperature lithium plating: during low-temperature fast charging, by adjusting the α value, i.e., adjusting the positive electrode release kinetics, the positive electrode lithium ion release rate can be better adapted to the negative electrode's embedding capability at low temperatures, avoiding the accumulation and deposition of lithium ions on the negative electrode surface due to the difference between the positive electrode supply and the negative electrode receiving lithium ion rates, thereby improving the battery's low-temperature charging safety and cycle stability.
[0023] The ratio of the Dv50 particle size of the negative electrode material to that of the positive electrode material is b. Adjusting the value of b affects the lattice diffusion path length, the number of interfacial reaction sites, and the pore structure and pore size distribution after the positive and negative electrode sheets are formed. Optimizing the compatibility of the above structure and sites affects the matching of the full-temperature-range kinetic rates of lithium-ion extraction from the positive electrode and lithium-ion insertion into the negative electrode, while also affecting the ion transport efficiency and interfacial charge transfer resistance under low-temperature fast charging, thereby fundamentally suppressing the nucleation and growth of lithium dendrites at low temperatures. Simultaneously, it enables lithium ions to rapidly and uniformly complete the entire process of extraction from the positive electrode lattice, transmembrane transport, and insertion into the negative electrode lattice under high-current fast charging, significantly improving the fast-charging acceptance capability of the secondary battery, and ultimately achieving synergistic optimization of low-temperature lithium plating suppression and fast-charging performance improvement.
[0024] In summary, this invention establishes the relationship n=a×b, while limiting n to satisfy 0.009≤n≤0.252, enabling precise dynamic matching and balance of positive and negative electrode dynamics. This design can simultaneously achieve the following two optimizations under low-temperature conditions: firstly, effectively suppressing lithium metal deposition, especially at low temperatures; and secondly, significantly improving the fast-charging performance of the secondary battery. Specifically, 'a' is adjusted to optimize the lithium-ion extraction rate of the positive electrode, and 'b' is adjusted to optimize the lithium-ion insertion rate of the negative electrode. Through the synergistic regulation of 'a' and 'b', a suitable balance between the positive electrode lithium-ion extraction rate and the negative electrode lithium-ion insertion rate is established, thereby reducing the rate difference between the two, effectively suppressing lithium metal deposition on the negative electrode surface, reducing irreversible lithium-ion consumption within the battery, and significantly improving the cycle life, capacity performance, and safety performance of the secondary battery. Furthermore, it can significantly optimize the extraction and insertion paths of lithium ions in the positive and negative electrodes, effectively improving the insertion rate of lithium ions after transport to the surface of the negative electrode material, achieving simultaneous optimization of low-temperature lithium deposition suppression and fast-charging performance.
[0025] The cathode material includes lithium iron phosphate. This invention does not limit the specific preparation method of lithium iron phosphate. Exemplarily, it can be prepared using the iron phosphate solid-state method, including the following steps:
[0026] 1) Mix the raw material mixture including iron phosphate and lithium source with deionized water to obtain positive electrode material slurry (solid content is 25~30%).
[0027] 2) Spray dry the cathode material slurry with an inlet temperature of 200~220℃, an outlet temperature of 85~95℃, and a spray rate of 600~800mL / h to obtain a spherical cathode material precursor.
[0028] 3) The spherical cathode precursor is pre-sintered under an inert atmosphere, heated to 380-420℃ at a rate of 3-5℃ / min, and held for 2-3 hours. After sintering, it is ground and sieved to obtain the pre-sintered cathode precursor.
[0029] 4) The pre-sintered cathode precursor is subjected to high-temperature sintering treatment. The temperature is increased to 700-850℃ at a rate of 1-2℃ / min under an inert atmosphere and held for 12-14 hours. After cooling, it is ground to a Dv50 particle size of 1-3μm and passed through a 200-mesh sieve to obtain lithium iron phosphate.
[0030] The mass ratio of iron phosphate to lithium source is 100:18.5~19.2. The Fe / P ratio of iron phosphate is 0.955~0.985, preferably 0.965~0.975. This invention does not limit the specific type of lithium source, including but not limited to at least one of lithium carbonate and lithium acetate.
[0031] It is understandable that, in addition to lithium iron phosphate, the cathode material also includes cathode binder and cathode conductive agent. Based on the mass percentage of the cathode material, the mass percentage of lithium iron phosphate is 96~99 wt%, the mass percentage of cathode binder is 0.8~3 wt%, and the mass percentage of cathode conductive agent is 0.2~2.0 wt%.
[0032] In addition to graphite-based materials, the negative electrode material also includes a negative electrode binder and a negative electrode conductive agent. Based on the mass percentage of the negative electrode material, the graphite-based material accounts for 96-98 wt%, the negative electrode binder accounts for 1.8-3.2 wt%, and the negative electrode conductive agent accounts for 0-1 wt%.
[0033] This invention does not specifically limit the preparation method of the negative electrode material. Exemplarily, in one specific embodiment, it may include the following steps:
[0034] 1) The graphite-based precursor is pre-calcined in an inert atmosphere at a temperature of 900-1200℃ for 2-4 hours, followed by pulverization to a Dv50 particle size of 5-12μm, and then classified to obtain pre-calcined powder with controllable particle size. A pulverizer can be used for pulverization at a speed of 1500-3500 rpm, preferably 1800-2800 rpm. A cyclone classifier can be used for classification at a speed of 2000-2800 rpm, preferably 2200-2600 rpm.
[0035] 2) Mix the pre-calcined powder with 5~20wt% asphalt compound, heat and knead at 200~300℃ to melt the asphalt compound and uniformly coat the surface of the pre-calcined powder, and then perform granulation to prepare precursor particles with a Dv50 particle size of 10~20μm.
[0036] 3) The precursor is graphitized at a temperature of 2500~3000℃ in an inert atmosphere to obtain graphite-based materials.
[0037] Graphite-based precursors include, but are not limited to, at least one of petroleum coke, needle coke, pitch coke, calcined coke, mesophase pitch microspheres, and anthracite.
[0038] This invention does not limit the specific type of negative electrode binder, including but not limited to at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; this invention does not limit the specific type of negative electrode conductive agent, including but not limited to at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0039] It is understood that the negative electrode sheet also includes a negative electrode current collector. The present invention does not limit the specific type of the negative electrode current collector, including but not limited to at least one of copper foil, nickel foam, and copper foam.
[0040] The present invention does not specifically limit the preparation method of the positive electrode sheet. Exemplarily, it may include the following steps: mixing lithium iron phosphate, positive electrode conductive agent and positive electrode binder, adding N-pyrrolidone (NMP) solvent, stirring until the system is homogeneous to obtain a positive electrode slurry; uniformly coating the positive electrode slurry on at least one side of the positive electrode current collector, and then drying, cold pressing and slitting to obtain a positive electrode sheet.
[0041] This invention does not specifically limit the preparation method of the negative electrode sheet. Exemplarily, it may include the following steps: mixing graphite-based material, negative electrode conductive agent, and negative electrode binder, and dispersing them in water to obtain a negative electrode slurry. Subsequently, the negative electrode slurry is uniformly coated on at least one surface of the negative electrode current collector, and then dried, rolled, and slit to obtain the negative electrode sheet.
[0042] The secondary battery of the present invention establishes a relationship between the ratio of the average DCR of the positive electrode to the average DCR of the secondary battery (a) and the ratio of the Dv50 particle size of the positive and negative electrodes (b) by systematically matching the physicochemical parameters of the positive and negative electrode materials and the positive and negative electrode sheets, using the formula n=a×b. At the same time, n satisfies 0.009≤n≤0.252, thereby achieving a dynamic balance between the dynamics of lithium ion extraction from the positive electrode and lithium ion insertion from the negative electrode, suppressing lithium plating and improving fast charging performance in low-temperature environments.
[0043] To further optimize the low-temperature performance of the secondary battery, in one specific embodiment, 0.03 ≤ n ≤ 0.108. When n meets this range, low-temperature lithium plating of the secondary battery is further suppressed, while its low-temperature fast-charging performance is improved.
[0044] In one specific implementation, 0.2 ≤ a ≤ 0.7. By adjusting the ratio 'a' of the average DCR of the positive electrode to the average DCR of the secondary battery to this range, the ion transport kinetics of the positive electrode can be significantly optimized, further reducing the kinetic difference between lithium ion extraction and insertion between the positive and negative electrodes. This optimizes the suppression of lithium metal deposition on the negative electrode surface and improves the rate performance and cycle stability of the secondary battery.
[0045] It should be noted that the Dv50 of lithium iron phosphate can be controlled by adjusting the high-temperature sintering temperature during the lithium iron phosphate preparation process or the Fe / P ratio of iron phosphate, thereby adjusting parameter 'a'. Specifically, the higher the sintering temperature, the larger the Dv50 particle size of lithium iron phosphate, and the larger the corresponding average DCR of the cathode, thus increasing 'a'; conversely, the smaller the Fe / P ratio, the larger the Dv50 of lithium iron phosphate, and thus increasing 'a'.
[0046] In one specific implementation, 0.04 ≤ b ≤ 0.4. By adjusting the ratio b of the negative electrode material Dv50 particle size to the positive electrode material Dv50 particle size to this range, the diffusion path of lithium ions can be significantly optimized, thereby improving the fast charging performance of the secondary battery.
[0047] It should be noted that b can be controlled by adjusting the Dv50 particle size of the positive or negative electrode materials. Specifically, the higher the sintering temperature during the lithium iron phosphate preparation process, the larger the Dv50 particle size of the lithium iron phosphate, and thus the larger b; or by adjusting the Fe / P ratio of the lithium iron phosphate, the smaller the Fe / P ratio, the larger the Dv50 of the lithium iron phosphate, and thus the larger b. Similarly, adjusting the rotation speed during the pulverization or classification process in the graphite-based material preparation process, the higher the rotation speed, the smaller the Dv50 of the graphite-based material, and thus the larger b.
[0048] To further suppress low-temperature lithium deposition on the negative electrode surface, in one specific embodiment, 0.3 ≤ a ≤ 0.6. This allows the secondary battery to achieve better rate performance and cycle stability.
[0049] To further improve the fast-charging performance of the secondary battery, in one specific implementation, 0.089 ≤ b ≤ 0.2, thereby achieving a more optimal level of fast-charging performance for the secondary battery.
[0050] In one specific implementation, the average DC internal resistance of the positive electrode is 30~200mΩ. By precisely adjusting the average DC resistance (DCR) of the positive electrode, the rate of lithium ion extraction from the positive electrode can be controlled, thereby regulating the lithium ion extraction kinetics of the positive electrode and further optimizing the suppression of metallic lithium deposition on the negative electrode surface.
[0051] In one specific implementation, the average DC internal resistance of the secondary battery is 60~300mΩ.
[0052] By adjusting the average DCR of the secondary battery to 60~300mΩ, the electron and ion transport efficiency inside the secondary battery can be significantly optimized, the heat release during charging and discharging can be reduced, and the fast charging performance, cycle performance and safety performance of the secondary battery can be improved.
[0053] In one specific embodiment, the Dv50 particle size of the cathode material is 0.6~2.0 μm. By controlling the Dv50 particle size of the cathode material within this range, not only can the lithium-ion extraction rate within the cathode be precisely controlled, reducing the mismatch in lithium-ion insertion / extraction kinetics between the positive and negative electrodes, but also the deposition of metallic lithium on the negative electrode surface can be further suppressed. Simultaneously, this Dv50 particle size range can also optimize the diffusion distance of lithium ions within the cathode particles, reducing the degree of interfacial polarization on the positive electrode side. This further alleviates the deposition of metallic lithium on the negative electrode side while significantly improving the lithium-ion diffusion rate and enhancing the fast-charging performance of the secondary battery.
[0054] In one specific embodiment, the Dv50 particle size of the anode material is 5~15μm. By controlling the Dv50 particle size of the anode material to this range, on the one hand, the lithium-ion insertion path can be optimized, promoting the rapid insertion of lithium ions into the anode material lattice and further suppressing low-temperature lithium plating; on the other hand, this Dv50 particle size range of the anode material can enhance the stability of the anode structure, thereby improving the integrity and durability of the SEI film structure on the anode surface, and thus significantly extending the cycle life of the secondary battery.
[0055] To specifically optimize the electrochemical performance of secondary batteries under harsh low-temperature environments, in one specific embodiment, the DC internal resistance of the positive electrode is 50~200mΩ at -10℃. By adjusting the DCR of the positive electrode to this range at -10℃, the difference in the rate of lithium ion insertion at the negative electrode and the rate of lithium ion extraction at the positive electrode under low-temperature conditions can be significantly reduced, thereby further suppressing the low-temperature lithium deposition phenomenon on the negative electrode surface. This allows the secondary battery to still maintain excellent capacity performance, cycle life, and safety under harsh low-temperature conditions.
[0056] To further optimize the fast-charging performance of secondary batteries in harsh low-temperature environments, in one specific embodiment, the DC internal resistance of the secondary battery is 100~400mΩ at -10℃. Adjusting the DCR of the secondary battery at this temperature can significantly optimize its charge transfer efficiency in low-temperature environments, thereby improving the low-temperature fast-charging performance of the secondary battery.
[0057] To further optimize the cycle life and safety performance of secondary batteries in low-temperature environments, in one specific embodiment, the DC internal resistance of the positive electrode is 20~200mΩ at 0℃.
[0058] To further optimize the low-temperature fast charging performance of the secondary battery, in one specific embodiment, the DC internal resistance of the secondary battery at 0°C is 40~300mΩ.
[0059] To further optimize the overall performance of the secondary battery, in one specific implementation, the DC internal resistance of the positive electrode is 10~80mΩ at 25℃.
[0060] To further optimize the fast-charging performance of the secondary battery, in one specific implementation, the DC internal resistance of the secondary battery at 25°C is 20~100mΩ.
[0061] To further improve the cycle life of secondary batteries, in one specific embodiment, the graphite-based material includes a graphite material matrix and a carbon coating layer disposed on at least a portion of the outer surface of the graphite material matrix.
[0062] Carbon coatings include carbon materials.
[0063] Specifically, by depositing a carbon coating layer on at least a portion of the outer surface of the graphite matrix, stable lithium-ion intercalation channels can be constructed on the graphite surface, significantly shortening the diffusion distance of lithium ions in the anode material. This also significantly reduces the anode interface impedance and prevents direct contact between the electrolyte and the graphite matrix, reducing interfacial side reactions. Based on optimizing the lithium-ion intercalation kinetics of the anode, this carbon coating layer significantly improves the cycle life of the secondary battery.
[0064] It should be noted that when the graphite-based material includes a carbon coating layer, its preparation steps also include carbon coating treatment of the graphitized product, which may include the following steps: after graphitization, the graphitized product and carbon material are uniformly mixed in deionized water, spray-dried, and then kept at 800~1200℃ for 12~18 hours. After depolymerization and sieving, the graphite-based material including the carbon coating layer is obtained. The mass ratio of the graphitized product to the carbon material is (90~99.5):(0.5~15).
[0065] It should be noted that this invention does not strictly limit the specific types of graphite matrix and carbon materials. Exemplarily, the graphite matrix includes, but is not limited to, at least one of petroleum coke, needle coke, mesophase carbon microspheres, graphitized carbon fibers, flake graphite, amorphous graphite, natural / artificial graphite composites, and graphite-soft / hard carbon composites. The carbon materials include, but are not limited to, at least one of coal tar, coal tar pitch, petroleum tar pitch, phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin, polyacrylonitrile, and carbohydrate organic compounds.
[0066] It should be noted that the mass ratio of the carbon coating layer to the graphite matrix is (0.5~15):(90~99.5). The thickness of the carbon coating layer is 1~20nm.
[0067] In one specific embodiment, lithium iron phosphate includes a lithium iron phosphate substrate and a coating layer disposed on at least a portion of the surface of the lithium iron phosphate substrate. The coating layer includes at least one of amorphous carbon, carbon nanotubes, graphene, Al2O3, and TiO2. This coating structure can further improve the ion transport performance of the cathode material, resulting in better rate performance of the secondary battery.
[0068] It should be noted that when lithium iron phosphate includes a coating layer, the raw material mixture during preparation also includes a carbon source. The mass ratio of lithium source to carbon source is (18.5~19.2):(10~12). The carbon source includes, but is not limited to, at least one of sucrose and glucose.
[0069] In one specific embodiment, the lithium iron phosphate matrix further includes doping elements, including at least one selected from Mg, Mn, Ni, Co, Al, and Ti. When the lithium iron phosphate has this composition, the cycle life and safety of the secondary battery are further improved.
[0070] It should be noted that when lithium iron phosphate includes doping elements, the raw material mixture during preparation also includes dopants. The mass ratio of lithium source to dopant is (38~40):(0.6~1.6). Dopants include, but are not limited to, at least one of the oxides, carbonates, nitrates, and fluorides of Mg, Mn, Ni, Co, Al, and Ti. It should also be noted that the content of doping elements in lithium iron phosphate is 300~5000 ppm.
[0071] It should be noted that parameter 'a' can also be controlled by adjusting the proportion of doping elements in lithium iron phosphate. The greater the doping amount, the greater the average DCR of the cathode, and thus the greater 'a'.
[0072] In one specific embodiment, the positive electrode material includes a positive electrode active material and a positive electrode conductive agent, wherein the amount of the positive electrode conductive agent is 0.1~2.0% based on the mass of the positive electrode active material.
[0073] By adjusting the amount of the positive electrode conductive agent to 0.1~2.0% of the mass of the positive electrode active material, the connectivity of the charge transport network inside the positive electrode can be improved, thereby effectively optimizing the battery's internal resistance. Simultaneously, the positive electrode conductive agent can act as a buffer medium, mitigating the volume expansion and contraction of the positive electrode active material during cycling and maintaining the integrity of the charge conduction network. By controlling the range of positive electrode conductive agent dosage, the fast-charging performance of the secondary battery can be significantly improved while enhancing the structural stability of the positive electrode sheet.
[0074] It should be noted that the present invention does not limit the specific type of positive electrode conductive agent, including but not limited to at least one of superconducting carbon black (SP), Ketjen black (KB), acetylene black (AB), single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), graphene nanosheets (GNPs), graphene oxide (GO), and reduced graphene oxide (rGO).
[0075] It is understood that the positive electrode material also includes a positive electrode binder. The present invention does not limit the specific type of positive electrode binder, including but not limited to at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), or functionally modified polymers of PVDF.
[0076] To further optimize the low-temperature electrochemical performance of the secondary battery, in one specific embodiment, the powder conductivity of the positive electrode conductive agent is 0.1~50 S / cm.
[0077] To further regulate the lithium-ion extraction rate of the positive electrode, in one specific embodiment, the porosity of the positive electrode sheet is 15-50%. Regulating the porosity of the positive electrode sheet to this range optimizes the lithium-ion diffusion path, resulting in more thorough electrolyte wetting and improved contact between the positive electrode conductive agent and the positive electrode active material. This ensures the integrity of the charge conduction network, thereby effectively regulating the impedance on the positive electrode side. Furthermore, this porosity provides a buffer for volume changes in the positive electrode material during cycling, significantly enhancing the structural stability of the positive electrode sheet.
[0078] In one specific embodiment, the porosity of the negative electrode sheet is 25-60%. By controlling the porosity of the negative electrode sheet within this range, the volume expansion of the negative electrode material during lithium-ion intercalation can be significantly alleviated, and its interfacial impedance can be reduced. Simultaneously, this porosity provides a rapid intercalation channel for lithium ions, thereby optimizing the lithium-ion intercalation rate, reducing lithium-ion accumulation on the negative electrode surface, fundamentally suppressing the problem of low-temperature lithium plating at the negative electrode, and significantly improving the discharge capacity and fast-charging performance of the secondary battery.
[0079] In one specific embodiment, the compaction density of the positive electrode sheet is 2.5~2.9 g / cm³. 3 .
[0080] By adjusting the compaction density of the positive electrode sheet to 2.5~2.9 g / cm³ 3 It can not only regulate the proportion of positive electrode active material per unit volume to achieve precise control of the energy density of secondary batteries, but also optimize the pore structure of the positive electrode to provide a buffer for volume changes during cycling, and optimize the continuity of charge conduction paths to improve the rate matching of electron conduction and ion diffusion. This simultaneously optimizes the structural stability and charge transport efficiency of the positive electrode, thereby improving the low-temperature cycle life and low-temperature fast charging performance of secondary batteries.
[0081] In one specific embodiment, the compaction density of the negative electrode sheet is 1.4~1.8 g / cm³. 3 .
[0082] By adjusting the compaction density of the negative electrode sheet to 1.4~1.8 g / cm³ 3It can optimize the pore structure of the negative electrode sheet and increase the proportion of negative electrode active material per unit volume, thereby effectively improving the lithium-ion insertion rate and lithium insertion capacity of the negative electrode. At the same time, it can also regulate the growth process of the SEI film on the negative electrode surface, helping to form a denser and more stable SEI film, thereby optimizing the interface impedance and concentration polarization, reducing the overall internal resistance of the negative electrode sheet, and further suppressing the lithium deposition phenomenon on the low-temperature negative electrode surface.
[0083] In one specific embodiment, the secondary battery further includes an electrolyte, which satisfies at least one of the following:
[0084] (1) The viscosity of the electrolyte is 1.0~5 mPa·s;
[0085] (2) The ionic conductivity of the electrolyte is 8~20 mS / cm.
[0086] It should be noted that the electrolyte, as the core diffusion medium for lithium ions, can significantly improve the lithium ion transport rate under low-temperature conditions by adjusting its viscosity to 1.0~5 mPa·s, thus optimizing the low-temperature fast-charging performance of secondary batteries. Simultaneously, it allows the electrolyte to more quickly wet the positive and negative electrode plates, forming more continuous ion transport channels. It is understandable that the electrolyte also contains additives; adjusting the electrolyte viscosity can effectively promote the rapid and uniform diffusion of these additives within the electrolyte system, allowing them to exert their effects.
[0087] To further optimize the lithium-ion transport rate, in one specific embodiment, the ionic conductivity of the electrolyte is 8~20 mS / cm.
[0088] The overall optimization of the electrolyte viscosity to 1.0~5 mPa·s and ionic conductivity to 8~20 mS / cm can effectively reduce the liquid phase transport resistance of lithium ions in the electrolyte, improve the lithium ion migration rate and transport efficiency, fundamentally improve the transport kinetics of lithium ions at low temperatures, and thus synergistically improve the overall low-temperature performance of secondary batteries, such as low-temperature charge and discharge, cycle stability and anti-lithium plating.
[0089] In one specific embodiment, the electrolyte comprises 80-95 wt% solvent, 0.2-4 wt% additives, and 4-18 wt% lithium salt. When the electrolyte has the above composition, its ionic conductivity is significantly optimized, while the interfacial charge transfer impedance is significantly reduced, thereby effectively improving the rate performance of the secondary battery. Simultaneously, this electrolyte system can induce the formation of a more uniform and dense SEI film on the negative electrode surface, further significantly improving the cycle life and safety performance of the secondary battery. This stable interfacial structure can effectively suppress interfacial side reactions during battery cycling, further enhancing the improvement effect on the cycle life and safety performance of the secondary battery.
[0090] In one specific embodiment, the solvent includes carboxylic acid ester compounds and carbonate compounds.
[0091] Specifically, carboxylic acid esters possess low cohesive energy and high molecular flexibility, and do not exhibit significant molecular aggregation even at low temperatures. Solvent systems comprising carboxylic acid esters and carbonate compounds can effectively regulate the overall viscosity of the electrolyte, thereby optimizing the lithium-ion transport rate, reducing ion transport hysteresis, and effectively suppressing concentration polarization. This further inhibits low-temperature lithium plating from the electrolyte transport perspective.
[0092] It should be noted that the mass ratio of carboxylic acid ester compound to carbonate compound is (2~70):(98~30).
[0093] It should be noted that carboxylic acid ester compounds include, but are not limited to, at least one of methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), methyl butyrate (MB), γ-butyrolactone (GBL), and δ-valerolactone (DVL).
[0094] Carbonate compounds include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate (DPC), and methyl ethyl carbonate (EMC).
[0095] To further optimize the overall performance of secondary batteries, in one specific embodiment, the additives include film-forming additives.
[0096] Specifically, adding film-forming additives to the electrolyte can preferentially cause reduction / oxidation decomposition on the electrode surface, forming a thin, dense, stable interface film with excellent ion conductivity and electronic insulation. This effectively blocks direct contact between the electrolyte and the electrode, inhibiting continuous electrolyte decomposition and gas generation. At the same time, it reduces interface impedance, decreases lithium-ion transport resistance, improves battery rate and fast-charging performance, protects the integrity of the electrode structure, reduces active lithium loss, and significantly improves the cycle stability, service life, and safety performance of the secondary battery.
[0097] It should be noted that the film-forming additives include, but are not limited to, at least one of the following: vinylene carbonate (VC), ethylene ethylene carbonate (VEC), fluoroethylene carbonate (VFEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 1,3-propanesulfonyl lactone (PS), 1,3-propenesulfonyl lactone (PES), trimethyl phosphate (TMP), triethyl phosphate (TEP), methanedisulfonate (MMDS), triphenyl phosphite (TPP), and vinyl sulfate (DTD).
[0098] In addition, additives may also include conductive additives, overcharge prevention additives, and flame retardant additives. This invention does not impose specific limitations on the specific types and amounts of the above-mentioned additives, and selection can be made according to performance requirements.
[0099] To optimize the electrochemical stability of the electrolyte, in one specific embodiment, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). When using the above-mentioned types of lithium salts, their high dissociation degree, excellent ion transport efficiency, and ability to induce the formation of a stable interface film on the electrode surface significantly improve the high-rate fast-charging performance, cycle life, high and low temperature adaptability, and safety performance of the secondary battery.
[0100] In one specific embodiment, the secondary battery further includes a separator; the separator has an air permeability of 80~400s / 100mL.
[0101] By adjusting the membrane's permeability to 80~400s / 100mL, a porous structure with good connectivity and uniform pore size can be formed within this range. On one hand, this improves the electrolyte's wetting effect on the membrane and enhances its liquid retention stability, thereby effectively reducing the resistance to lithium-ion transport across the membrane. On the other hand, it enables faster and more uniform lithium-ion transport under low-temperature conditions, reducing localized lithium-ion accumulation on the negative electrode surface, thus significantly optimizing the low-temperature cycle performance of the secondary battery and effectively suppressing low-temperature lithium plating.
[0102] It should be noted that the diaphragm includes a diaphragm substrate and a diaphragm functional layer. The specific material type of the diaphragm substrate is not limited, but includes, but is not limited to, at least one of polyethylene (PE), polypropylene (PP), PP / PE / PP, polyethylene terephthalate (PET), and polyimide (PI). The present invention also does not limit the specific composition of the diaphragm functional layer. In one specific embodiment, it includes, but is not limited to, at least one of alumina, boehmite, lithium aluminum titanium phosphate (LATP), silica (SiO2), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), aramid fiber, poly(p-phenylenebenzodioxazole) (PBO), PI, and wood fiber.
[0103] The present invention does not limit the specific preparation method of the diaphragm. For example, it can be: using PE as the diaphragm substrate, applying alumina as coating 1 on both sides or one side with a micro-concave roller, and then spraying polyvinylidene fluoride as coating 2 on the base film or coating 1 to obtain the diaphragm.
[0104] Secondly, the present invention also provides an electrical device, including the aforementioned secondary battery. This electrical device broadly refers to various devices or systems that rely on electrical energy for operation, particularly including mobile or stationary equipment that uses electrical energy as a power source for all or part of its operation. Exemplarily, the device can be a transportation vehicle, such as a conventional internal combustion engine vehicle, a gas-powered vehicle, or a vehicle driven by new energy sources, wherein new energy vehicles can further include pure electric vehicles, hybrid vehicles, range-extended electric vehicles, etc.
[0105] Besides vehicles, this electrical equipment can also encompass other terminal products that rely on energy storage devices for operation, such as communication terminals (e.g., mobile phones), portable computing devices (e.g., tablets and laptops), consumer electronics (e.g., digital media players, electric toys), work tools (e.g., power tools), and various vehicles (e.g., electric ships, drones). Furthermore, in the aerospace field, this equipment can also include aircraft, launch vehicles, spacecraft, and other devices that require high-energy-density power systems.
[0106] By adopting the secondary battery provided by this invention, the above-mentioned electrical equipment can simultaneously improve in terms of low-temperature fast charging performance and safety, which is conducive to improving the overall performance and reliability of the equipment and is suitable for diversified application scenarios with high requirements for power systems.
[0107] The secondary battery provided in this application establishes a relationship between the ratio a of the average DCR of the positive electrode to the average DCR of the secondary battery and the ratio b of the Dv50 particle size of the positive and negative electrodes through systematic matching of the physicochemical parameters of the positive and negative electrode materials, with the formula n=a×b. The formula is limited to 0.009≤n≤0.252. This achieves a dynamic balance between the dynamics of lithium ion extraction from the positive electrode and lithium ion insertion from the negative electrode, thereby suppressing lithium plating and simultaneously improving fast charging performance in low-temperature environments.
[0108] The secondary battery of this application will be further described in detail below through specific embodiments.
[0109] Example 1
[0110] The secondary battery in this embodiment is prepared through the following steps:
[0111] 1) Cathode preparation: Iron phosphate (Fe / P = 0.985), lithium carbonate, and sucrose were mixed in a mass ratio of 100:18.8:10, and TiO2 was added to achieve a Ti dopant content of 3000 ppm. Deionized water was added to form a cathode material slurry with a solid content of 28 wt%. The cathode material slurry was spray-dried using a spray dryer at an inlet air temperature of 210℃, an outlet air temperature of 90℃, and a spray rate of 750 mL / h to obtain the cathode material precursor. The cathode material precursor was pre-sintered by heating to 400℃ at a rate of 3.5℃ / min in air and holding for 2.5 hours. The resulting material was then ground and sieved to obtain the pre-sintered cathode precursor. The pre-sintered cathode precursor was then subjected to high-temperature sintering by heating to 700℃ at a rate of 1.4℃ / min and holding for 12 hours. After cooling, grind until Dv50 is 1.1μm, and pass through a 200-mesh sieve to obtain lithium iron phosphate.
[0112] Lithium iron phosphate, a positive electrode active material, Super P, a conductive agent, and PVDF, a binder, are mixed in a mass ratio of 96:2:2. NMP solvent is added, and the mixture is stirred under vacuum in a double planetary slurry reactor until the system is homogeneous to obtain a positive electrode slurry. The positive electrode slurry is then uniformly coated on both sides of an aluminum foil, dried in an oven, and then cold-pressed and slit to obtain a positive electrode sheet.
[0113] 2) Preparation of negative electrode sheet: Petroleum coke was pre-calcined at 1000℃ for 3 hours in an inert atmosphere, followed by pulverization (2100 rpm) and classification (2400 rpm of the classifier wheel) to obtain pre-calcined powder. The pre-calcined powder was then mixed with asphalt at a mass ratio of 95:5, kneaded at 250℃, and granulated to obtain precursor particles. These particles were then graphitized in a graphitization furnace at 3000℃ for 8 hours, and after natural cooling to room temperature, dispersed to obtain a graphite matrix. The graphite matrix (92g), asphalt (6g), and water were uniformly mixed, then spray-dried and held at 950℃ for 3 hours. Finally, after deagglomeration and sieving, artificial graphite (with a carbon coating thickness of 9nm and a coating rate of 68%) was obtained.
[0114] Artificial graphite, conductive agent Super P, binder CMC, and binder SBR were mixed in a mass ratio of 96.0:1.0:1.2:1.8 to obtain the negative electrode material (BET is 1.5m). 2 / g, graphitization degree of 93%), and dispersed in water to obtain negative electrode slurry. Then the negative electrode slurry is evenly coated on both sides of copper foil, and after drying, rolling and slitting, negative electrode sheet is obtained.
[0115] 3) Electrolyte preparation: Methyl acetate (30g), ethylene carbonate (30g), and ethyl methyl carbonate (55g) are mixed to obtain an organic solvent. Then, fully dried lithium salt LiPF6 (14g) is dissolved in the mixed organic solvent, and film-forming additives such as vinylene (2g) are added to prepare an electrolyte with a viscosity of 4mPa·s (ionic conductivity of 10mS / cm).
[0116] 4) Separator Preparation: PE was used as the separator substrate (7μm thick). High-purity alumina nanoparticles were mixed and ground with a dispersion medium and additives to form a uniform slurry. The slurry was then uniformly coated onto the surface of the base membrane using a microgravure coating method as coating layer 1. After drying and curing, a 2μm thick ceramic coating was formed. Finally, an adhesive layer was prepared by spraying. A suitable adhesive was selected and mixed with solvent to form a uniform adhesive solution, which was then uniformly sprayed onto the surfaces of coating layer 1 and the PE base membrane, with a controlled thickness of 3μm. After drying and curing to remove residual solvent, a complete separator was obtained.
[0117] 5) Assemble the secondary battery: The positive electrode, separator, and negative electrode are stacked in sequence so that the separator is placed between the positive and negative electrodes to isolate them. Then, the cells are wound to obtain the bare cells. The bare cells are placed in the outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, and shaping, the secondary battery 1 is obtained.
[0118] Example 2
[0119] This embodiment is basically the same as Embodiment 1, except that the high-temperature sintering temperature in step 1) is adjusted to 820℃ and the Fe / P ratio is adjusted to 0.96. The pulverization speed in step 2) is adjusted to 2300 rpm. This embodiment yields secondary battery 2.
[0120] Example 3
[0121] This embodiment is basically the same as Embodiment 1, except that the high-temperature sintering temperature in step 1) is adjusted to 760℃, and the amount of dopant is adjusted to make the Ti element doping amount 2500ppm. The pulverization speed in step 2) is adjusted to 1900rpm. This embodiment yields secondary battery 3.
[0122] Example 4
[0123] This embodiment is basically the same as Embodiment 3, except that the Fe / P ratio in step 1) is adjusted to 0.975. The pulverizing speed in step 2) is adjusted to 2100 rpm, and the grading speed is adjusted to 2200 rpm. This embodiment yields secondary battery 4.
[0124] Example 5
[0125] This embodiment is basically the same as Embodiment 3, except that the high-temperature sintering temperature in step 1) is adjusted to 790℃ and the Fe / P ratio is adjusted to 0.97. The grading rotation speed in step 2) is adjusted to 2400 rpm. This embodiment yields secondary battery 5.
[0126] Example 6
[0127] This embodiment is basically the same as Embodiment 1, except that in step 1), the Fe / P ratio is adjusted to 0.965, and the amount of dopant is adjusted so that the Ti doping amount is 500 ppm. This embodiment yields secondary battery 6.
[0128] Example 7
[0129] This embodiment is basically the same as Embodiment 5, except that the crushing speed in step 2) is adjusted to 2700 rpm, and the grading wheel speed in the grading process is adjusted to 2800 rpm. This embodiment yields secondary battery 7.
[0130] Example 8
[0131] This embodiment is basically the same as Embodiment 6, except that the temperature of the high-temperature sintering treatment in step 1) is adjusted to 820℃. The pulverizing speed in step 2) is adjusted to 1500 rpm, and the classifying wheel speed in the classifying treatment is adjusted to 2200 rpm. This embodiment yields a secondary battery 8.
[0132] Example 9
[0133] This embodiment is basically the same as Embodiment 1, except that the Fe / P ratio in step 1) is adjusted to 0.985; and the pulverization speed in step 2) is adjusted to 2500 rpm, and the grading speed is adjusted to 2700 rpm. This embodiment yields a secondary battery 9.
[0134] Comparative Example 1
[0135] This comparative example is basically the same as Example 1, except that the high-temperature sintering temperature in step 1) is adjusted to 850°C, the Fe / P ratio is 0.975, and the amount of dopant is adjusted to make the Ti element doping amount 1000ppm; the pulverizing speed in step 2) is 1500rpm, and the grading speed is 2000rpm. This comparative example yields a secondary battery 10.
[0136] Comparative Example 2
[0137] This comparative example is basically the same as Example 1, except that the high-temperature sintering temperature in step 1) is adjusted to 850°C and the Fe / P ratio is adjusted to 0.955; the pulverizing speed in step 2) is adjusted to 1900 rpm and the grading speed is adjusted to 2000 rpm. This comparative example yields a secondary battery 11.
[0138] Comparative Example 3
[0139] This comparative example is basically the same as Example 1, except that the high-temperature sintering temperature in step 1) is adjusted to 820℃, the Fe / P ratio is 0.965, and the amount of dopant is adjusted to make the Ti element doping amount 4500ppm; the pulverizing speed in step 2) is 3500rpm, and the grading speed is 2400rpm. This comparative example yields a secondary battery 12.
[0140] Experimental Example 1
[0141] The structural performance testing of the positive electrode, negative electrode, electrolyte, and separator in all embodiments and comparative examples includes the following steps.
[0142] 1. Porosity test
[0143] The porosity of the positive and negative electrodes was measured using mercury intrusion porosimetry. The porosity was denoted as K, with units of %.
[0144] 2. Compacted density test
[0145] The rolled electrode sheet was punched to a regular size, and edge burrs were removed. At room temperature, using a thickness gauge with an accuracy of at least 0.001 mm, five evenly distributed measuring points were selected in the effective coating area of the electrode sheet to measure the thickness, and the arithmetic mean was taken. The mass of the electrode sheet was weighed using an electronic balance, and the effective area of the electrode sheet was measured and calculated. The result was obtained by calculating the compaction density using the formula: Compacted density = Electrode mass / (Effective area × Electrode thickness). Each group of samples was tested in parallel three times, and the average value was taken as the test result. The unit is g / cm³. 3 .
[0146] 3. Electrode conductivity test
[0147] The conductivity of the positive electrode was measured using the four-probe method, with units of S / cm.
[0148] 4. Electrolyte viscosity test
[0149] The viscosity of the electrolyte was measured at 25℃ using a digital viscometer, with units of mPa·s.
[0150] 5. Electrolyte conductivity test
[0151] A conductivity electrode (platinum black electrode) and an electrochemical workstation were used. Before testing, the electrode constant was calibrated with standard KCl solution, and the electrode must be dry and clean. Electrolyte was injected into the electrode test cell, air bubbles were removed, and the cell was placed in a constant temperature bath at 25℃±0.1℃ for 30 minutes to ensure temperature stability. Test parameter settings: frequency range 10... 5 Hz~10 -1 Hz, AC excitation voltage 5mV, impedance spectrum was collected and solution resistance was obtained using the high-frequency intercept. Conductivity was calculated using the formula κ=Kcell / R calculation, where K cell Let be the electrode constant, and R be the measured resistance.
[0152] 6. Diaphragm air permeability test
[0153] The air permeability of the diaphragm was measured using a Grylls air permeability meter, with units of s / 100mL.
[0154] Experimental Example 2
[0155] The secondary batteries of all embodiments and comparative examples were subjected to the following tests, and the results are shown in Table 1.
[0156] 1. Dv50 particle size test
[0157] Scanning electron microscopes were used to photograph the positive and negative electrode materials, and the Dv50 particle size of the positive and negative electrode materials was calculated using a scale bar. The unit is μm.
[0158] 2. DC internal resistance test of the positive electrode plate
[0159] A pouch cell is assembled with positive electrode, negative electrode, and separator in a 6-positive-7-negative configuration. A copper wire is inserted between the negative electrode and the separator, and an additional separator is used to separate the negative electrode and the copper wire. After liquid is injected and the mixture is brought to a constant volume, lithium is plated onto the copper wire using a small current to obtain the reference electrode.
[0160] The battery was placed in a 25°C constant temperature chamber and charged to 50% SOC using 0.33C. After standing for 40 minutes, the positive terminal-reference voltage V was read. 0(OCV) Apply a discharge pulse: constant current I discharges for 10 seconds, record the voltage V1 between the positive terminal and the reference at the end of the discharge, and calculate using the formula DCR=(V 0(OCV) The DCR of the positive electrode at 0℃ and -10℃ can be calculated by adjusting the oven temperature and performing the same test and calculation steps as described above.
[0161] 3. DC internal resistance test of secondary batteries
[0162] Adjust the charge to 50% SOC using 0.33C, let it stand for 40 minutes, and then read the voltage V between the positive and negative terminals. 0(OCV) Apply a discharge pulse: discharge at a constant current I for 10 seconds, record the voltage V1 between the positive and negative terminals at the end of the discharge, and calculate using the formula DCR=(V 0(OCV) The DCR of a secondary battery at 0°C and -10°C can be calculated by adjusting the oven temperature and performing the same tests as described above.
[0163] Table 1 Parameters of secondary batteries
[0164]
[0165] Experimental Example 3
[0166] The electrochemical performance of the secondary batteries in all examples and comparative examples was tested as follows, and the results are shown in Table 2.
[0167] 1. Fast charging performance test
[0168] Fast charging performance tests were conducted on the secondary batteries of Examples 1-9 and Comparative Examples 1-3. The test process is as follows:
[0169] At 25℃, the battery was charged at a constant current of 0.02C for 300 minutes, then left to stand for 10 minutes. It was then charged at a constant current of 0.1C for 300 minutes, left to stand for 1 hour to complete formation, and finally charged at a constant current and constant voltage of 0.33C to a full charge of 3.8V. It was then discharged at 0.33C to 2V, charged at a constant current of 0.33C to 3.8V, charged at a constant voltage to the cutoff current of 0.05C, and then discharged at a constant current of 0.33C to 2V. The discharge capacity was recorded as the standard capacity Q0 at 0.33C.
[0170] At 0℃, the battery was charged at a constant current of 2C to a negative parameter potential of 0mV, then charged at a constant current of 1.6C to a negative parameter potential of 0mV, and then charged at a constant current of 1.2C to a negative parameter potential of 0mV. This process was repeated to reduce the current to 0.8C, 0.6C, 0.4C, 0.3C, 0.2C, and 0.1C, charging to a negative parameter potential of 0mV. Finally, the battery was discharged at 0.33C to a terminal voltage of 2.0V, and the standard capacity Q1 at 0.33C was recorded. The fast-charging capacity retention rate was obtained using the formula: Fast-charging capacity retention rate = (Q1 / Q0) × 100%. The test was repeated 3 times. (Unit: %)
[0171] 2. Cyclic performance test
[0172] The secondary batteries of Examples 1-9 and Comparative Examples 1-3 were subjected to cycle performance tests at 0°C. The test procedure was as follows: The battery under test was charged at a constant current of 0.02C for 300 minutes at 0°C, and then allowed to stand for 10 minutes; then charged at a constant current of 0.1C for 300 minutes, and allowed to stand for 1 hour to complete battery formation. The battery was then charged at a constant current and constant voltage of 0.33C to 3.65V to full charge, and then discharged at a constant current of 0.33C to 2V; subsequently, it was charged at a constant current of 0.33C to 3.8V and then charged at a constant voltage to the cutoff current of 0.05C, and finally discharged at a constant current of 0.33C to 2.0V. The discharge capacity was recorded as the 0.33C standard capacity Q0.
[0173] The battery was placed in a 0℃ environment and charged sequentially at a constant current of 2C to a negative parameter potential of 0mV, 1.6C, and 1.2C, with the current gradually reduced to 0.8C, 0.6C, 0.4C, 0.3C, 0.2C, and 0.1C, each time charging to a negative parameter potential of 0mV to complete fast charging. After fast charging, the battery was discharged at a constant current of 0.33C to a terminal voltage of 2.0V, which was recorded as one cycle. This process was repeated 100 times, and the discharge capacity at 100 cycles was recorded. The capacity retention rate after 100 cycles was calculated as follows: Capacity retention rate after 100 cycles = (Discharge capacity after 100 cycles / Q0) × 100%. Each battery group was tested three times, and the average value of the test results was taken. The unit is %.
[0174] Table 2 Electrochemical performance of secondary batteries
[0175]
[0176] As shown in Table 2, the battery of the present invention can effectively improve the fast charging capacity retention rate and the capacity retention rate after 100 cycles under low temperature conditions by constructing the relationship n=a×b, while n satisfies 0.009≤n≤0.252, thus achieving simultaneous optimization of the battery's low temperature fast charging performance and cycle life.
[0177] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A secondary battery, characterized in that, The secondary battery includes a positive electrode and a negative electrode. The positive electrode includes a positive electrode material layer, and the positive electrode material layer includes a positive electrode material. The negative electrode includes a negative electrode material layer, and the negative electrode material layer includes a negative electrode material. The positive electrode material includes lithium iron phosphate, and the negative electrode material includes graphite-based materials; The ratio of the average DC internal resistance of the positive electrode to the average DC internal resistance of the secondary battery is a. The ratio of the Dv50 particle size of the positive electrode material to the Dv50 particle size of the negative electrode material is b; n = a × b, where 0.009 ≤ n ≤ 0.
252.
2. The secondary battery according to claim 1, characterized in that, 0.03≤n≤0.108。 3. The secondary battery according to claim 1, characterized in that, 0.2≤a≤0.7; and / or, 0.04≤b≤0.4。 4. The secondary battery according to claim 1, characterized in that, 0.3≤a≤0.6; and / or, 0.089≤b≤0.2。 5. The secondary battery according to claim 1, characterized in that, The average DC internal resistance of the positive electrode is 30~200mΩ; and / or, The average DC internal resistance of the secondary battery is 60~300mΩ.
6. The secondary battery according to claim 1, characterized in that, The Dv50 particle size of the positive electrode material is 0.6~2.0 μm; and / or, The particle size of the Dv50 of the negative electrode material is 5~15μm.
7. The secondary battery according to claim 1, characterized in that, At -10℃, the DC internal resistance of the positive electrode is 50~200mΩ; and / or, At -10℃, the DC internal resistance of the secondary battery is 100~400mΩ.
8. The secondary battery according to claim 1, characterized in that, At 0°C, the DC internal resistance of the positive electrode is 20~200mΩ; and / or, At 0°C, the DC internal resistance of the secondary battery is 40~300mΩ; and / or, At 25°C, the DC internal resistance of the positive electrode is 10~80mΩ; and / or, At 25°C, the DC internal resistance of the secondary battery is 20~100mΩ.
9. The secondary battery according to any one of claims 1-8, characterized in that, The graphite-based material includes a graphite matrix and a carbon coating layer disposed on at least a portion of the outer surface of the graphite matrix. The carbon coating layer comprises carbon materials.
10. The secondary battery according to any one of claims 1-8, characterized in that, The lithium iron phosphate comprises a lithium iron phosphate matrix and a coating layer disposed on at least a portion of the surface of the lithium iron phosphate matrix, the coating layer comprising at least one of amorphous carbon, carbon nanotubes, graphene, Al2O3, and TiO2; and / or, The lithium iron phosphate matrix also includes doping elements, which include at least one of Mg, Mn, Ni, Co, Al, and Ti.
11. The secondary battery according to any one of claims 1-8, characterized in that, The positive electrode material includes a positive electrode active material and a positive electrode conductive agent, and the amount of the positive electrode conductive agent is 0.1~2.0% based on the mass of the positive electrode active material.
12. The secondary battery according to claim 11, characterized in that, The powder conductivity of the positive electrode conductive agent is 0.1~50 S / cm.
13. The secondary battery according to any one of claims 1-8 or 12, characterized in that, The porosity of the positive electrode sheet is 15-50%; and / or, The porosity of the negative electrode is 25-60%.
14. The secondary battery according to any one of claims 1-8 or 12, characterized in that, The compaction density of the positive electrode sheet is 2.5~2.9 g / cm³. 3 ; and / or, The compaction density of the negative electrode sheet is 1.4~1.8 g / cm³. 3 .
15. The secondary battery according to any one of claims 1-8 or 12, characterized in that, The secondary battery further includes an electrolyte, which satisfies at least one of the following: (1) The viscosity of the electrolyte is 1.0~5 mPa·s; (2) The electrolyte has an ionic conductivity of 8~20 mS / cm.
16. The secondary battery according to claim 15, characterized in that, The electrolyte comprises 80-95 wt% solvent, 0.2-4 wt% additives, and 4-18 wt% lithium salt.
17. The secondary battery according to claim 16, characterized in that, The solvent includes carboxylic acid ester compounds, carbonate compounds; and / or, The additives include film-forming additives; and / or, The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
18. The secondary battery according to any one of claims 1-8, 12, or 16-17, characterized in that, The secondary battery also includes a separator; The air permeability of the diaphragm is 80~400s / 100mL.
19. An electrical appliance, characterized in that, The secondary battery includes any one of claims 1-18.
Citation Information
Patent Citations
Negative pole piece and application thereof
CN116314612A
Lithium ion secondary battery
CN121149367A